Bain & company and SARS : a massive failure of governance and integrity - Sieff, Grant; Hofmeyr, Katherine (London : Wits Business School, 2022)
In 2014, South African Revenue Service (SARS) commissioner, Tom Moyane, embarked upon a restructuring of the tax authority based on plans drawn up by international consulting firm Bain & Company. The consequences were devastating and far-reaching, both for SARS and the economy. Moyane was fired in early 2018 and retired Judge Robert Nugent's Commission of Inquiry into Tax Administration and Governance by SARS ran from June to October 2018. Although Bain denied any wrongdoing, Vittorio Massone, its managing partner for sub-Saharan Africa, had had a closer relationship with Moyane than initially had been disclosed. Bain ultimately admitted to "significant errors of judgement", but how might the company avoid such a situation in future?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Taxation -- South Africa; Fiscal policy -- South Africa; South Africa -- Economic conditions